Criblage De Quelques Genotypes De Ble Dur (Triticum Durum Desf.) Sous Un Stress Salin En Culture De Pot - Ayed, Sourour; Othmani, Afef; Beji, Sadreddine; Amara, Hajer (European Scientific Journal, ESJ, 2016)
In this study, five durum wheat (Triticum turgidum ssp durum) genotypes: Agili, Arbi, Derbassi, Karim and Maali were assessed for 04 agronomical parameters associated with salinity-tolerance. Genotypes were grown under glasshouse conditions and exposed to five salinity levels (control, 3g/l, 6 g/l, 9 g/l et 12 g/l of NaCl) to evaluate their tolerance using their biomass and the relative salt-susceptibility index: R.S.S.I = R.B.D./S.I.I. (R.B.D.: relative biomass deficit and S.I.I.: salinity intensity index).Genotypic screening was also based on agro-morphological traits: tillers number/plant, plant height, grains number/spike and 1000 kernel weight. Analysis of variance revealed a significant (p<0.001) difference between treatments and genotypes. This difference indicated a large variability between genotypes. Results showed also that Maali variety had the higher agronomic performance and the lower R.S.S.I than other genotypes.